Persona, shadow, and the divided self: A Jungian reading of individuation in The Scarlet Letter - Abbas, Syed Zamanat; Pandey, Ashish (Research Journal in Advanced Humanities, 2026)
This paper attempts a psychoanalytic reading of the novel The Scarlet Letter by Nathaniel Hawthorne using the Jungian framework of Persona or the social mask, Shadow or the hidden self, and individuation or the integration of the two elements of psyche. It moves beyond the traditional readings of the novel in terms of feminism and psychoanalytic readings that used Freudian framework of libidinal repression, and tries to see repression in broader Jungian terms of social, moral, and spiritual terms. By applying the Jungian framework of Persona, Shadow, and Individuation, the paper claims that individuation was possible in Hester Prynne because her guilt was exposed and her Shadow was visible to all. Due to his social position, Dimmesdale is forced to wear the mask of virtue which makes him suffer psychic disintegration; his health deteriorates and he ultimately dies. This critiques the Puritan techniques of moral and social surveillance that turns the private acts into a public spectacle of morality. It uses qualitative textual analysis, comparative and contrastive study of the characters and psychoanalytic and historicist approaches to show that visible wound like that of Hester Prynne is easy to heal while a hidden wound like Dimmesdale’s can be fatal.